Effectiveness of Immunization on Prevention of Diseases Among Children 0-60 Months of Age in Esan West Local Government Ekpoma, Edo State:Implications for Counselling - Osumah, Obaze Agbonluae; Edeme-Okonigene, Dorcas (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
Infant mortality from vaccine-preventable diseases (VPDs) remains a public health problem. Low immunization coverage can hamper the effectiveness of infectious disease prevention in infants. This study aims to analyze the effectiveness of immunization in preventing VPD, increasing the body's resistance to infection, and reducing infant mortality. This study used a quantitative approach with a descriptive survey design. The study population consisted of 150 women, with all of them being sampled using the total sampling technique. Data were collected through a questionnaire that had been tested for validity by health experts and tested for reliability using the test-retest method. Data analysis was conducted using descriptive statistics, including frequencies, percentages, and averages, with the help of SPSS version 22. The results showed that immunization is effective in preventing VPD, increasing infants' resistance to infectious diseases, and reducing infant mortality. The conclusion of this study confirms that immunization is a significant health intervention in reducing the risk of infection and infant mortality. The implications of this study emphasize the importance of educating mothers about the benefits of immunization and the need for community-based strategies to increase immunization coverage.